2004
DOI: 10.1002/anie.200460547
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Cycloheptadienol Derivatives by a Formal [5+2] Carbocyclization Reaction of α,β,γ,δ‐Diunsaturated (Methoxy)carbene Complexes with Methyl Ketone Lithium Enolates

Abstract: Magnificent seven! Functionalized seven‐membered carbocycles can be easily synthesized in a diastereoselective way by a formal [5+2] carbocyclization reaction from dienylmethoxycarbene complexes and methyl ketone lithium enolates (see scheme). Examples for R: Ph, 2‐Fu, PhCH2CH2, TMSCC; R1: H, Me; R2: Ph, 2‐Fu are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…According to the proposed mechanism, an 1,2 addition of lithium enolate to dienylcarbene complex 81 provides intermediary 84 , with the chair‐like transition state driving stereoselectivity. Further internal 1,4 addition promoted by a 1,2 metal shift results in 85 , which evolves to 83 by means of hydrolysis and double bond isomerization (Scheme 14B) [113] …”
Section: Fischer Carbene Complexes With Metal‐mediated Higher‐order Cycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the proposed mechanism, an 1,2 addition of lithium enolate to dienylcarbene complex 81 provides intermediary 84 , with the chair‐like transition state driving stereoselectivity. Further internal 1,4 addition promoted by a 1,2 metal shift results in 85 , which evolves to 83 by means of hydrolysis and double bond isomerization (Scheme 14B) [113] …”
Section: Fischer Carbene Complexes With Metal‐mediated Higher‐order Cycloadditionsmentioning
confidence: 99%
“…After elimination of this group, the coordination of the double bond results in the formation of species 138 . The synthesis is completed with the hydrolysis and decoordination of the metal fragment to deliver the derivatives of cycloheptadienol 135 (Scheme 23B) [113] …”
Section: Fischer Carbene Complexes With Metal‐mediated Higher‐order Cycloadditionsmentioning
confidence: 99%
“…Barluenga et al have reported a conceptually different [5 + 2] cycloaddition reaction of lithium enolates and Fischer carbene complexes (Scheme ) . Both tungsten and chromium complexes mediate the stoichiometric reaction, with superior yields obtained in the tungsten manifold.…”
Section: Fischer Carbene-mediated [5 + 2] Cycloaddition Reactionsmentioning
confidence: 99%
“…Thus, apart from the [2+2] and [4+2] cyclization reactions involving the activated CC and C⋮C bond of α,β-unsaturated carbene complexes, the most characteristic and valuable reactions are those wherein the metal−carbon bond is involved. Thus, a number of carbocyclization reactions based on two components, e.g., [2+1], [3+1], [3+2], [3+3], , [4+1], 8i, [4+3], 8d,10b,c, [5+1], and [5+2], as well as on various components, e.g., [2+2+1], [3+2+1], [3+2+2], [4+2+1], [5+2+1], [2+2+1+1], 14d, and [2+2+2+1],16a have been reported in the recent past.…”
Section: Introductionmentioning
confidence: 99%